The ethnographic self as resource writing memory and experience into ethnography - Collins, Peter 1954-; Gallinat, Anselma; IG Publishing (New York Berghahn Books, 2010)
It is commonly acknowledged that anthropologists use personal experiences to inform their writing. However, it is often assumed that only fieldwork experiences are relevant and that the personal appears only in the form of self-reflexivity. This book takes a step beyond anthropology at home and auto-ethnography and shows how anthropologists can include their memories and experiences as ethnographic data in their writing. It discusses issues such as authenticity, translation and ethics in relation to the self, and offers a new perspective on doing ethnographic fieldwork.
The ethnographic self as resource: an introduction / Peter Collins and Anselma Gallinat -- Playing the native card: the anthropologist as informant in Eastern Germany / Anselma Gallinat -- Foregrounding the self in fieldwork among rural women in Croatia / Lynette Šikić-Mićanović -- Some Reflections on the "enchantments" of village life, or whose story is this? / Anne Kathrine Larsen -- The ethics of participant observation: personal reflections on fieldwork in England / Nigel Rapport -- Ethnographers as language learners: from oblivion and towards an echo / Alison Phipps -- Leading questions and body memories: a case of phenomenology and physical ethnography in the dance interview / Jonathan Skinner -- Dualling memories: twinship and the disembodiment of identity / Donna Lee Davis and Dorothy I. Davis -- Remembering and the ethnography of children's sports / Noel Dyck -- Gardening in time: happiness and memory in American horticulture / Jane Nadel-Klein -- The role of serendipity and memory in experiencing fields / Tamara Kohn -- Serendipities, uncertainties and improvisations in movement and migration / Vered Amit -- On remembering and forgetting in writing and fieldwork / Simon Coleman -- The ethnographic self as resource? / Peter Collins -- Epilogue: what a story we anthropologists have to tell! / James W. Fernandez.
Electronic reproduction.
Keywords: Ethnology -- Authorship; Ethnology -- Biographical methods; Ethnology -- Fieldwork; Electronic books